Determination of Benzalkonium Chloride in Nasal Drops by High-Performance Liquid Chromatography - Danijela A. Kostić; Snezana S. Mitić; Danijela Č. Nasković; Aleksandra R. Zarubica; Milan N. Mitic (E-Journal of Chemistry)
A high-performance liquid chromatography (HPLC) system was used in the reversed phase mode for the determination of benzalkonium chloride (BKC) in nosal drops. A Chromolit RP-18e, 100 x 4.6, (UM6077/035) column was used at 40 °C. The mobile phase, optimized through an experimental design, was a 70:30 (v/v) mixture of 0.057M Na-heksansulphonate potassium, dihydrogen orthophosphate buffer (pH 2.9) and acetonitrile, pumped at a flow rate of 1.75 mL/min at maintaining column temperature at 40 °C. Maximum UV detection was achieved at 215 nm. The method was validated in terms of selectivity, linearity, repeatability, precision and accuracy. The method was successfully applied for the determination of BKC in a pharmaceutical formulation of nasal drop solution without any interference from common excipients and drug substance. All the validation parameters were within the acceptance range, concordant to ICH guidelines.